2016
DOI: 10.1186/s12935-016-0352-z
|View full text |Cite|
|
Sign up to set email alerts
|

Relationship between TRAF6 and deterioration of HCC: an immunohistochemical and in vitro study

Abstract: ObjectiveTo explore the relationship between tumor necrosis factor receptor-associated factor 6 (TRAF6) and the clinicopathological features in HCC as well as its biological function.MethodsTotally, 412 liver tissues were collected, including 171 hepatocellular carcinoma (HCC) and their corresponding non-tumor tissues, 37 cirrhosis and 33 normal liver tissues. The expression of TRAF6 was assessed by immunohistochemistry. Then, analysis of the correlations between TRAF6 expression and clinicopathological parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 34 publications
(33 reference statements)
1
15
0
Order By: Relevance
“…Corroborating initial evidence, intestinal epithelial cell-specific TRAF6 −/− mice exhibit exacerbated DSS-induced colitis ( 87 ). In line with the in vivo data, knockdown of TRAF6 or inhibition of TRAF6 E3 ligase activity suppresses the survival, proliferation, migration, and metastasis of many human epithelial cancers, including breast, lung, liver, and colon cancers as well as HNSCC ( 230 232 , 236 240 ). In the majority of these cases, the TRAF6-NF-κB axis is identified as the main oncogenic pathway, which is constitutively activated by TRAF6 overexpression or hyperactivated by upstream receptors such as TNFα, RANK, and TLR4/3 ( 236 240 ).…”
Section: Traf6supporting
confidence: 69%
“…Corroborating initial evidence, intestinal epithelial cell-specific TRAF6 −/− mice exhibit exacerbated DSS-induced colitis ( 87 ). In line with the in vivo data, knockdown of TRAF6 or inhibition of TRAF6 E3 ligase activity suppresses the survival, proliferation, migration, and metastasis of many human epithelial cancers, including breast, lung, liver, and colon cancers as well as HNSCC ( 230 232 , 236 240 ). In the majority of these cases, the TRAF6-NF-κB axis is identified as the main oncogenic pathway, which is constitutively activated by TRAF6 overexpression or hyperactivated by upstream receptors such as TNFα, RANK, and TLR4/3 ( 236 240 ).…”
Section: Traf6supporting
confidence: 69%
“…TRAF6 is well known as an E3 ubiquitin ligase important for inflammatory signaling . Recent studies have indicated that TRAF6 is involved in HCC development . However, the regulatory mechanisms of TRAF6 in HCC remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have indicated that TRAF6 plays critical roles in cancer . Elevated TRAF6 expression is observed in HCC . However, the mechanisms of the oncogenic function of TRAF6 in HCC remain uncharacterized.…”
mentioning
confidence: 99%
“…The IRAK1 antibody (F-4, sc-5228, 1:50 dilution) provided by Santa Cruz Biotechnology (Heidelberg, Germany) was used for IHC detection. The detailed protocol of IHC was shown in our previous studies 20,21. The IRAK1 staining in HCC cells was analyzed through blind evaluation, which was performed by two pathologists who independently identified the intensity of staining and the positive staining ratio of IRAK1.…”
Section: Methodsmentioning
confidence: 99%